2010
DOI: 10.5194/acp-10-4241-2010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of dust aerosol by combining CALIPSO active lidar and passive IIR measurements

Abstract: Abstract. The version 2 Cloud-Aerosol Lidar and InfraredPathfinder Satellite Observations (CALIPSO) dust layer detection method, which is based only on lidar measurements, misclassified about 43% dust layers (mainly dense dust layers) as cloud layers over the Taklamakan Desert. To address this problem, a new method was developed by combining the CALIPSO Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) and passive Infrared Imaging Radiometer (IIR) measurements. This combined lidar and IR measurement (h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…The CALIOP mask shows a complex situation with aerosols detected at different altitudes between the sea surface and 6 km that are potentially embedded with some optically thin cloudy structures. We observe some abrupt changes in the CALIOP results that we assume to be artificial for the most part since the CALIOP mask is sometimes subject to misclassification between aerosol and cloud layers, especially when dense dust layers are encountered (Chen et al, 2010). The CALIOP results obtained for the case study on mineral dust particles acquired on 4 August 2008 are reported in Fig.…”
Section: Mineral Dust Aerosolsmentioning
confidence: 91%
“…The CALIOP mask shows a complex situation with aerosols detected at different altitudes between the sea surface and 6 km that are potentially embedded with some optically thin cloudy structures. We observe some abrupt changes in the CALIOP results that we assume to be artificial for the most part since the CALIOP mask is sometimes subject to misclassification between aerosol and cloud layers, especially when dense dust layers are encountered (Chen et al, 2010). The CALIOP results obtained for the case study on mineral dust particles acquired on 4 August 2008 are reported in Fig.…”
Section: Mineral Dust Aerosolsmentioning
confidence: 91%
“…Guan et al (2015a) found that the enhanced warming in drylands was a result of radiativeforced temperature, which has a close relationship with aerosol column burden. The aerosol in drylands has an obvious warming effect (Huang et al, 2006aChen et al, 2010;Ye et al, 2012;Jin et al, 2015), and the aerosol has a wide distribution and tends to have a relatively large optical depth (H. Bi et al, 2011;Liu et al, 2011;, leading to a significant radiative effect in the drylands. According to the results of Tegen and Fung (1995), the existing atmospheric dust load is hard to explain by natural sources alone.…”
Section: Introductionmentioning
confidence: 99%
“…The corrected data mask also agrees with the BTD values of MODIS. For comparison of LDF applicability, results from LDF developed by Chen et al (2010) (hereafter referred to as LDF') are shown in Fig. 9c.…”
Section: Reclassification Of the Cloud Layers In The Caliop Cloud Maskmentioning
confidence: 99%
“…The corresponding data mask is rarely different from the data mask before the LDF correction, which indicates that LDF' is less effective than LDF in this study. The reason for false detection by LDF' is that Chen et al (2010) did not collect training data during the nighttime, resulting in uncertainties in the true PDF, which is needed for creating an accurate discrimination model. These two demonstrations of the discriminant analysis result in the successful reclassification of dust over land and sea during the daytime and nighttime.…”
Section: Reclassification Of the Cloud Layers In The Caliop Cloud Maskmentioning
confidence: 99%
See 1 more Smart Citation